Evaluating citizen science outreach: A case-study with The Peregrine Fund's American Kestrel Partnership. - Sarah E Schulwitz; Greg C Hill; Vanessa Fry; Christopher J W McClure (PLoS ONE)
Citizen science programs can be powerful drivers of knowledge and scientific understanding and, in recent decades, they have become increasingly popular. Conducting successful research with the aid of citizen scientists often rests on the efficacy of a program's outreach strategies. Program evaluation is increasingly recognized as a critical practice for citizen science practitioners to ensure that all efforts, including outreach, contribute to the overall goals of the program. The Peregrine Fund's American Kestrel Partnership (AKP) is one such citizen science program that relies on outreach to engage participants in effective monitoring of a declining falcon species. Here, we examine whether various communication strategies were associated with desired outreach goals of the AKP. We demonstrate how social media, webcams, discussion boards, and newsletters were associated with perception of learning, agreement with our conservation messaging, and participation in our box monitoring program. Our results thus help us to improve our outreach methodology, suggest areas where other citizen science programs might improve their outreach efforts, and highlight future research priorities.